The sin of white supremacy: Christianity, racism, and religious diversity in America - Hill Fletcher, Jeannine (Orbis Books, 2017)
How Christian supremacy gave birth to white supremacy -- The witchcraft of white supremacy -- When words create worlds -- The symbolic capital of New Testament love -- The cruciform Christ -- Christian love in a weighted world